(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome, also referred to as Müllerian agenesis, is the second most common cause of primary amenorrhea. It is characterized by congenital aplasia or absence of the uterus, cervix, and the upper 2/3 of the vagina in phenotypically normal 46, XX females. Embryological evidence shows that MRKH syndrome occurs due to the failure of Müllerian ducts devel opment, which in turn leads to a poorly developed vagina, cervix, uterus or even an absence of either organ. Usually patients present at puberty due to primary amenorrhea. So, mostly they visit to gynecological department but manage ment is multi-model and multi-disciplinary. In this study, we have presented our experience of management of MRKH syndrome. Materials and methods: A prospective observational study was being carried out in BSMMU from Oct. 2018 to Oct. 2021. A total 27 patients were diagnosed with MRKH syndrome. A total 27 patients were diagnosed with MRKH syndrome and evaluated for classification by X-ray, ultrasonography, hormonal evaluation and MRI for selected cases. Results:A total 27 patients were evaluated among them 9 patients were operated under paediatric surgery department. Patients age ranged from 13-18 years, mean age was 15.1 years. Type I MRKH syndrome patients were 11 and Type II MRKH syndrome were 16. We had treated 4 cases of Type-I and 5 cases of Type-II MRKH syndrome. Conclusion:Management of MRKHS is challenge in Bangladesh perspective. Surgery is not only the treatment but main focus should be in counselling for next conjugal and social life. Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 21-24